Hybrid Electric Vehicle Car Body Drag Analysis using Computational Fluid Dynamics - D., Ramasamy; Mohanesan, K; K., Kadirgama; M. M., Noor; M. M., Rahman (Universiti Malaysia Pahang, 2017)
Aerodynamics drag was considered for giving better efficiency for a car on the road. The development of drag on a vehicle body was studied. The main objective was to determine the maximum drag occurring on the car body drag of the hybrid electric vehicle (HEV). The analysis was conducted on the car speed ranging between 40 km/h to 110 km/h using pressure points at various parts of the car. The car body was modelled in CAD using the mass and momentum equations discretized for an analysis. The technique to estimate the drag used was input of car body-drag (CFD) and exporting it to finite element analysis (FEA) to find the value of aerodynamics drag in terms of drag forces and drag coefficient. The values were validated with actual pressure reading from pressure probes on the car body. The result showed that contour and trajectories plots were also used to analyse the characteristics of streamlines flow or boundary layer occurred on the body of this model, especially for the forebody, upper body and rear body. The maximum rise of aerodynamics drag occurred between velocities of 80 km/h and 90 km/h which was about 5.04 % increase of drag coefficient. Further analysis is required with wind tunnels.